An Analysis of College Students’ Perceptions on Domestic Minor Sex Trafficking in Pine Bluff, Arkansas - Wheat, Janette; Shavers, Patricia; Bailey, Marilyn (International Journal for Innovation Education and Research, 2020)
Domestic minor sex trafficking (DMST) is modern-day slavery of children and the commercial sexual abuse of children through buying, selling, or trading their sexual services. DMST is a form of child abuse. The victim can be any person of nationality, age, socioeconomic status, or gender. In America, throughout college campuses, a lot of students are not informed of domestic minor sex trafficking. When thinking about domestic minor sex trafficking, most people do not think that this crime happens in our country, better yet our state of Arkansas. The purpose of this study was to investigate the perceptions of college students attending the University of Arkansas at Pine Bluff on domestic minor sex trafficking in our country and in our state of Arkansas (a crime that is growing aggressively in the United States). Fifty participants who were students attending the University of Arkansas at Pine Bluff participated in the study. Participants consisted of male and female students between the ages of 18 to 25 (N = 30 Females; N = 20 Males). Survey data were analyzed using Microsoft Excel software. Participants responded to ten yes or no descriptive questions about domestic minor sex trafficking (e.g., Questions like: have you heard about domestic minor sex trafficking; and do you think child sex trafficking is an organized crime). The data yielded both quantitative and qualitative results. Results showed that female students were more knowledgeable and were more aware of DMST than males. Implications for interventions will be discussed. Further research also is suggested.